Nanotechnology-assisted recycling of textile waste : sustainable tools for textiles - Sharma, Prashansa; Sahay, Shilpi Shree (John Wiley & Sons, Inc. ; Scrivener Publishing LLC, 2025)
Discover how innovative nanotechnology can turn waste into opportunity, offering insights and strategies to create a greener, more eco-friendly textile industry. This book investigates nanotechnology-assisted sustainable solutions and their potential to transform waste into opportunity by fostering innovative designs and in-depth knowledge of sustainable waste management and nanotechnology applications. Divided into four comprehensive parts, comprising 16 chapters, Nanotechnology Assisted Recycling of Textile Waste, provides insights into the potential of nanotechnology in revolutionizing textile recycling and shaping the future of sustainable textiles. Part I sets the stage with an insightful overview of textile waste and management, exploring the conceptual dimensions and challenges in handling and organizing textile waste. It also describes the innovative realm of textile recycling. In Part II, the spotlight shines on comprehensive, sustainable, and productive recycling of waste using nanotechnology. Here, readers are invited to explore the transformative contributions of nanotechnology in shaping sustainable textile design and characterizing functional properties of novel recycled nano-textiles. Future perspectives of nanotechnology in textile applications, particularly concerning waste recycling, are also examined. Part III explores deeper into the advanced application of recycled and nano-assisted novel textiles generated through waste. From sports textiles to technical textiles, this section explores the diverse applications of recycled waste, bolstered by nano-engineered innovations. Finally, Part IV addresses the critical aspects of quality control and regulatory compliance in the realm of advanced nano-textile materials through an exploration of global legislation, schemes, and standards. Readers will find in this book: research findings and innovative approaches to cope with the challenges and issues of textile waste; systematic and scientific knowledge on textile waste recycling techniques using nanotechnology; knowledge of complex scientific research findings in a simple and understandable form; comprehensive coverage of a broad range of topics, including sustainable textile waste management. Audience The book will be read by a range of researchers, engineers and students in technical textiles, textile technology and engineering, textile chemistry, fiber science, textile processing technologies and manufacturing, fashion and apparel technology, materials science, environmental science. This book will help designers and clothing manufacturers, and all those in textile and environmental domains, who are engaged in waste management.
Keywords: Textile fabrics -- Recycling.; Textile fibers -- Recycling.; elektronické knihy; electronic books